The histamine H4 receptor mediates inflammation and Th17 responses in preclinical models of arthritis. Issue 3 (14th October 2013) - Cowden, Jeffery M; Yu, Fuqu; Banie, Homayon; Farahani, Mandana; Ling, Ping; Nguyen, Steven; Riley, Jason P; Zhang, Mai; Zhu, Jian; Dunford, Paul J; Thurmond, Robin L
Abstract : Objective: The histamine H4 receptor (H4 R) has been shown to drive inflammatory responses in models of asthma, colitis and dermatitis, and in these models it appears to affect both innate and adaptive immune responses. In this study, we used both H4 R-deficient mice and a specific H4 R antagonist, JNJ 28307474, to investigate the involvement of the H4 R in mouse arthritis models. Methods: H4 R-deficient mice and wild-type mice administered the H4 R antagonist were studied in models of collagen antibody-induced arthritis (CAIA) and collagen-induced arthritis (CIA). The impact on Th17 cells was assessed by restimulation of inguinal lymphocytes in the disease or immunisation models and with in vitro stimulation of whole blood. Results: Both H4 R-deficient mice and mice treated with the H4 R antagonist exhibited reduced arthritis disease severity in both CAIA and CIA models. This was evident from the reduction in disease score and in joint histology. In the CIA model, treatment with the H4 R antagonist reduced the number of interleukin (IL)-17 positive cells in the lymph node and the total production of IL-17. Th17 cell development in vivo was reduced in H4 R-deficient mice or in mice treated with an H4 R antagonist. Finally, treatment of both mouse and human blood with an H4 R antagonist reduced the production of IL-17 when cells were stimulated in vitro. Conclusions: These results implicate the H4 R in disease progression in arthritis and in the production of IL-17 from Th17 cells. This work supports future clinical exploration of H4 R antagonists for the treatment of rheumatoid arthritis.